Evaluating the Effect of Active Charcoal-Containing Toothpaste on Color Change, Microhardness, and Surface Roughness of Tooth Enamel and Resin Composite Restorative Materials - Ali Forouzanfar; Pouria Hasanpour; Yasaman Yazdandoust; Hosein Bagheri; Hamideh Sadat Mohammadipour (International Journal of Dentistry)
Background and Objectives. Charcoal-containing toothpastes have become popular among many patients; however, there is inadequate scientific evidence on oral health. This study aimed to evaluate the color change, surface microhardness, and roughness of bovine enamel and composite resin submitted to simulated toothbrushing with a whitening toothpaste containing activated charcoal. Methods. Thirty-six bovine incisors and resin composite samples were prepared, stained with black tea, and then randomly divided into two groups. The samples were brushed with a charcoal-containing toothpaste (Colgate® MAX WHITE) and daily toothpaste (Colgate® Max Fresh) for 10,000 cycles. Before and after brushing cycles, color variables (ΔL, Δa, Δb), total color change (ΔE), plus Vickers microhardness were evaluated. Two samples of each group were prepared for surface roughness assessment via atomic force microscope. Data were analyzed by Shapiro–Wilk, Independent sample t-test and Mann–Whitney U tests. Results. According to the obtained results, ΔE and ΔL were significantly higher whereas Δa and Δb were noticeably lower in charcoal-containing toothpaste group in comparison with daily toothpaste in both composite and enamel samples. The microhardness of samples brushed with Colgate® MAX WHITE was significantly higher than that of Colgate® Max Fresh in enamel (P=0.04), whereas no significant difference was found in composite resin samples (P=0.23). Colgate® MAX WHITE enhanced the roughness of both enamel and composite surfaces. Conclusion. The charcoal-containing toothpaste could improve the color of both enamel and resin composite with no negative effect on microhardness. Nevertheless, its adverse roughening effect should be considered occasionally on composite restorations.